Systematic Literature Review : Peran Kepemimpinan Wanita dalam Meningkatkan Kolaborasi dan Kinerja Sumber Daya Manusia - Titis Tatasari; Mochamad Fatchurrohman (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
Women's leadership is recognized as a strategic factor driving organizational success through the formation of effective and sustainable team collaboration. Beyond simply directing, women leaders build a conducive work climate where team members are valued, engaged, and have equal opportunities to contribute. Across various sectors, they demonstrate the ability to manage team dynamics with a participatory, collaborative approach, and a focus on healthy interpersonal relationships. This study uses the Systematic Literature Review (SLR) method to describe the role, benefits, and challenges of women's leadership in human resource (HR) development. Twelve articles published between 2020 and 2024 were selected based on the PICOC framework to ensure academic validity. The study results indicate that women's leadership is synonymous with a participatory style, empathy, and open communication that encourages time commitment, the flow of ideas, innovation, and productivity. Women leaders create a psychologically safe work environment, value differences of opinion, and encourage cross-functional collaboration. Their role is increasingly important in the era of flexible work and digital transformation, where empathy and communication are key to maintaining team motivation and productivity. However, challenges such as gender stereotypes, structural barriers, and cultural resistance still limit the effectiveness of women's leadership, especially in strategic positions and high-level decision-making. In many cases, women leaders still have to work harder to gain legitimacy, even though they have the same or even higher qualifications than their male counterparts. Addressing this requires more inclusive organizational policies, gender-based leadership training programs, mentoring, and consistent advocacy for equality. Companies and public institutions must actively create an ecosystem that supports women's leadership development, including equal access to strategic career opportunities.